Modelling individual and competitive adsorption of cadmium(II) and zinc(II) metal ions from aqueous solution onto bagasse fly ash - Srivastava V.C.; Mall I.D.; Mishra I.M. (My University, 2025)
The present study deals with the competitive adsorption of cadmium (Cd(II)) and zinc (Zn(II)) ions onto bagasse fly ash (BFA) from binary systems. BFA is a waste obtained from the bagasse-fired boilers of sugar mills. The initial pH≈6.0 is found to be the optimum for the individual removal of Cd(II) and Zn(II) ions by BFA. The equilibrium adsorption data were obtained at different initial concentrations ( C 0 = 10-100 mg/l), 5 h contact time, 30°C temperature, BFA dosage of 10 mg/l at pH 0 = 6. The Redlich-Peterson (R-P) and the Freundlich models represent the single ion equilibrium adsorption data better than the Langmuir model. The adsorption capacities in the binary-metal mixtures are in the order Zn(II)>Cd(II) and is in agreement with the single-component adsorption data. The equilibrium metal removal decreases with increasing concentrations of the other metal ion and the combined action of Cd(II) and Zn(II) ions on BFA is found to be antagonistic. Equilibrium isotherms for the binary adsorption of Cd(II) and Zn(II) ions on BFA have been analyzed by non-modified Langmuir, modified Langmuir, extended-Langmuir, Sheindorf-Rebuhn-Sheintuch (SRS), non-modified R-P and modified R-P adsorption models. The isotherm model fitting has been done by minimizing the Marquardt's percent standard deviation (MPSD) error function using MS Excel. The SRS model satisfactory fits for most of the adsorption equilibrium data of Cd(II) and Zn(II) ions onto BFA.